Revisiting Meiosis in Sugarcane: Chromosomal Irregularities and the Prevalence of Bivalent Configurations - Vieira, Maria Lucia C.; Almeida, Carmelice B.; Oliveira, Carlos A.; Tacuatiá, Luana O.; Munhoz, Carla F.; Cauz-Santos, Luiz A.; Pinto, Luciana R.; Monteiro-Vitorello, Claudia B.; Xavier, Mauro A.; Forni-Martins, Eliana R. (Frontiers in Genetics, 2018)
Traditional sugarcane cultivars (Saccharum officinarum) proved highly susceptible to diseases, and this led breeders to progress to interspecific crosses resulting in disease resistance. A backcrossing program to S. officinarum was then required to boost sucrose content. Clonal selection across generations and incorporation of other germplasm into cultivated backgrounds established the (narrow) genetic base of modern cultivars (Saccharum spp.), which have a man-made genome. The genome complexity has inspired several molecular studies that have elucidated aspects of sugarcane genome constitution, architecture, and cytogenetics. However, there is a critical shortage of information on chromosome behaviour throughout meiosis in modern cultivars. In this study, we examined the microsporogenesis of a contemporary variety, providing a detailed analysis of the meiotic process and chromosome association at diakinesis, using FISH with centromeric probes. Chromosomal abnormalities were documented by examining high quality preparations of pollen mother cells (700 in total). Approximately 70% of the cells showed abnormalities, such as metaphase chromosomes not lined up at the plate, lagging chromosomes and chromosomal bridges, and tetrad cells with micronuclei. Some dyads with asynchronous behavior were also observed. Due to the hybrid composition of the sugarcane genome, we suggest that bivalent incomplete pairing may occur in the first prophase leading to univalency. The presence of rod bivalents showing the lagging tendency is consistent with a reduction in chiasma frequency. Finally, the presence of chromatin bridges indicates the indirect occurrence of chromosomal inversions, although chromosome fragments were not clearly recognized. Possible reasons for such meiotic abnormalities and the large prevalence of bivalent formation are discussed.